Behaviour of a Clay and Gravel Mixture - Ali Firat Cabalar; Sarwar Omer Hama; Suleyman Demir (The Baltic Journal of Road and Bridge Engineering)
In most construction works, crushed rock aggregates with angular shape are used as subgrade materials. However, naturally available rounded granular aggregates could be utilized in design of subgrade layers as an alternative material for economic and environmental reasons. Therefore, a comparative study on the road pavement subgrade using aggregates of two different shapes (angular and rounded) of the same size (10–19 mm) has been conducted in this paper. The California Bearing Ratio and unconfined compressive strength tests were carried out on the mixtures of clay and different contents (0%, 5%, 10%, 15%, and 20% by dry weight) of both aggregates in order to evaluate the influence of the shape of these aggregates on the testing results. It was found that the mixtures with the rounded gravels showed a greater maximum dry density, unconfined compressive strength and CBR value, as well as lower optimum water content value, than those with the angular gravels.